KNOWLEDGE MANAGEMENT IN THE AMAZON REGION: INTEGRATING TRADITIONAL KNOWLEDGE, DIGITAL INNOVATION, AND PUBLIC POLICIES FOR SUSTAINABLE DEVELOPMENT - Ziviani, Fabricio; da Cunha, Willey Roney Oliveira Motta; Correia, Christiane de Miranda e Silva; de Oliveira, Silvana Alves; Pontes, Deysiane Farias; Mariz, Flávio Medeiros; Lemos, Karina Dutra de Carvalho; Piacentini, Marcos Tadeu Simões; da Silva, Helton Junior; Piacentini, Alexandre Leonardo Simões; Dias, Ademilson de Assis; Adamy Neto, Nery; et al. (Seven Editora, 2025)
Knowledge Management (KM) has increasingly consolidated as a strategic approach to sustainable development and innovation across regional contexts. In the Amazon region, characterized by vast biodiversity and sociocultural complexity, KM plays a crucial role in integrating traditional and scientific knowledge, promoting environmental conservation, and fostering sustainable socioeconomic development. This article discusses key challenges and opportunities for KM in Amazonia, focusing on the interfaces among science, technology, public policy, and local communities. Accordingly, the study examines how KM can be applied to preserve, systematize, and valorize Amazonian traditional knowledge while promoting innovation oriented toward sustainable development. It also identifies knowledge co-construction practices, challenges related to the inclusion of Indigenous peoples and local communities, and the political and institutional implications for territorial and environmental governance. The methodology combines a bibliometric review, interviews with KM researchers working in Amazonian contexts, government reports, an analysis of the trajectories of research groups, and a review of the scientific literature on KM in Amazonia. The results highlight the need for participatory conceptual models, transparency in data governance, and the institutionalization of inclusive dialogue channels. Recommendations are also presented for public policy and research practice. DOI: https://doi.org/10.56238/sevened2025.036-114